Information and promotion genre regarding korean content in netflix press release - Nursyahbani, Novi (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2021)
This research at the beginning discusses the development of press releases that have been developed into various aspects, ranging from the media used, the themes presented, to the genres classified in a study. Departing from the research of Catenaccio (2008), this study wants to examine the structure created from that research, whether it is still relevant today and can show informative and promotional genres in a press release. Thanks to its freedom to be applied in various types of press releases, this research will choose a company based from a data that mentioned company that gained many profit during the Covid-19 pandemic and had many products released, which is Netflix. Data collection and analysis methods used in this study were convenience sampling and structural analysis from Catenaccio. Through convenience sampling, there are three articles selected up to June 15, those published on May 27, June 06 and June 10, 2021. The result of the analysis is that the structure of Catenaccio which contains the format of writing press releases, does not match the format of writing press releases in Netflix, but main points such as leads, justifying the product, detailing the product and explicit promotional components still applicable and determine the genre in press releases. The genres of Netflix press releases are hybrid because they contain an informative and promotional genre. A new structure that has been modified in this study is also offered for further research, with a wider selection of press release articles and other data collection techniques.